The multiple mini-interviews: The experience from a saudi postgraduate residency program toward a more objective selection process - Khalid Mohammed Alayed; Walid Alkeridy; Musa Alzahrani (Wolters Kluwer Medknow Publications, 2021)
Purpose: The multiple mini-interview (MMI) is a validated technique used in the admissions process in some undergraduate and postgraduate schools and is reported to reduce subjectivity in selecting postgraduate applicants. No studies have been conducted in Saudi Arabia concerning the MMI. The authors report their experience of transitioning from traditional interviews to the MMI and the results of a post-MMI survey undertaken by participating applicants and interviewers. Materials and Methods: The authors did retrospective analysis after MMI had been conducted at the College of Medicine, King Saud University, Riyadh, Saudi Arabia, in 2019, in coordination with an internal medicine residency program. They implemented MMIs totaling four stations of 10 min each that focused on the domains of communication, attitude, knowledge, and a mini-interview personalized for each candidate. Ten questioners interviewed 99 applicants, of whom 68 undertook a post-MMI survey. Results: In terms of their perceptions and experience, the applicants and interviewers responded positively to the transition from traditional interviews to the MMI. MMI was seen to be more objective, 75% of applicants felt it was associated with less anxiety, and 79% believed it provided a better portrayal of their abilities. Conclusion: The use of the MMI in selecting postgraduate applicants in Saudi Arabia is feasible and acceptable. Furthermore, it may give an improved objective portrayal of applicants' abilities and reduce their interview-associated anxiety.